2022
DOI: 10.1128/jb.00494-21
|View full text |Cite
|
Sign up to set email alerts
|

Acinetobacter baumannii Regulates Its Stress Responses via the BfmRS Two-Component Regulatory System

Abstract: Acinetobacter baumannii is a common nosocomial pathogen that utilizes numerous mechanisms to aid its survival in both the environment and in the host. Coordination of such mechanisms requires an intricate regulatory network. We report here that A. baumannii can directly regulate several stress-related pathways via the two-component regulatory system, BfmRS. Similar to previous studies, results from transcriptomic analysis showed that mutation of the BfmR response regulator c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
60
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(66 citation statements)
references
References 77 publications
(117 reference statements)
5
60
1
Order By: Relevance
“…In fact, we show that modulation of motility by light in A. baumannii V15 depends on both components of this system, BfmR and BfmS. Our working model is compatible with BfmR acting as a repressor of motility most likely in its phosphorylated state, which is counteracted by BfmS in the dark most probably by dephosphorylation 11 , setting thus a differential response to illumination that is lost in the absence of the repressor, independently of the light condition (Fig. 6).…”
Section: Discussionsupporting
confidence: 69%
See 3 more Smart Citations
“…In fact, we show that modulation of motility by light in A. baumannii V15 depends on both components of this system, BfmR and BfmS. Our working model is compatible with BfmR acting as a repressor of motility most likely in its phosphorylated state, which is counteracted by BfmS in the dark most probably by dephosphorylation 11 , setting thus a differential response to illumination that is lost in the absence of the repressor, independently of the light condition (Fig. 6).…”
Section: Discussionsupporting
confidence: 69%
“…In fact, analyses of RNAseq data performed in ATCC 17978 strain by Geisinger et al, 2018, show that bfmS expression is reduced in the ΔbfmR mutant (FCbfmR in ΔbfmS = 1.467; FCbfmS in ΔbfmR = 0,0308), indicating that BfmR acts as an activator of bfmRS expression. Consistently, it has been shown that BfmR can activate its own expression, and phosphorylation is required for autoinduction 11 . As control, the ΔbfmRS mutant harboring the empty pUC_AcORI_Ptac_TER_lacIq2 plasmid 12 , which is referred to as pE, behaved as ΔbfmRS, i.e., does not photoregulate and moved both under blue light and in the dark (Fig.…”
Section: Resultsmentioning
confidence: 59%
See 2 more Smart Citations
“…Two-component systems (TCSs) also play an important part in A. baumannii stress resistance, biofilm formation, and drug resistance, primarily by regulating the signal transduction of environmental stimuli. At least 7 TCSs have been described in A. baumannii thus far , including AdeSR [ 5 ], BaeSR [ 6 ], BfmSR [ 7 ], GasSA [ 8 ], PmrAB [ 9 ], StkSR [ 10 ], and A1S_2811 of A. baumannii ATCC 17978 [ 11 ], and have been associated with aromatic compound catabolism, motility, biofilm formation, virulence, and drug resistance [ 12 ].…”
Section: Introductionmentioning
confidence: 99%